Parasites (Monogenea) of tilapias Oreochromis niloticus and Coptodon rendalli (Cichlidae) in a river spring in Brazil - Ebert, Mariana Bertholdi [UNESP]; Narciso, Rodrigo Bravin [UNESP]; Vieira Dias, Diego Henrique Miranda [UNESP]; Osaki-Pereira, Melissa Miyuki [UNESP]; Jorge, Maurício [UNESP]; de León, Gerardo Pérez-Ponce; da Silva, Reinaldo José [UNESP] (EDP Sciences, 2024)
In the present study, we examined 30 individuals of introduced African cichlids, Oreochromis niloticus and Coptodon rendalli, collected in a river spring of the Pardo River, Paranapanema River basin, southeastern Brazil. Based on morphological and molecular analyses of the partial LSU rDNA gene, we identified four species of monogeneans, Cichlidogyrus tilapiae, C. thurstonae, C. mbirizei, and Scutogyrus longicornis on the gills of O. niloticus, whereas individuals of C. rendalli were infested only with C. papernastrema. This is the first record of C. mbirizei and C. papernastrema in tilapias from Brazil. The ecological consequences of the introduction of exotic species of tilapia such as O. niloticus and C. rendalli along with their monogenean parasites in a wild environment represented by a river spring are discussed. Our new molecular data on Cichlidogyrus and Scutogyrus contribute to the investigation of the phylogenetic interrelationships of these widely distributed genera of monogeneans since their species composition is still unsettled.
Parasites (Monogenea) des tilapias Oreochromis niloticus et Coptodon rendalli (Cichlidae) dans une source au Brésil
Keywords: Cichlidogyrus; Exotic fishes; LSU rDNA; Monogenea; Neotropical region; Scutogyrus